Antibiotic Usage and its Sensitivity Pattern in the NICU - Shrestha, R; Shrestha, JM; Gurung, B (Kathmandu University Medical Journal, 2013)
Background Sepsis is a major cause of mortality and morbidity in newborns affecting both developed and developing countries accounting a quarter around one million deaths per annum. Objective This study was aimed to assess the prevalence of neonatal sepsis, culture isolates, pattern, antibiotic sensitivity and drug prescribing pattern. Methods In present prospective study, 48 neonates admitted in pediatric ward from January to March 2011 of Dhulikhel Hospital were included. The gestation age, onset of sepsis, culture isolates, antibiotic sensitivity pattern and drug prescribing pattern were studied. Environmental air sampling of NICU (Neonatal Intensive Care Unit) was done by settle plate method for microbial examination. Result Among 48 neonates, 23 (47.92%) neonates were culture positive with predominant isolates of Klebsiella oxytoca 11(47.83%), Pseudomonas spp. 4(17.39%), Methicillin Resistant Staphylococcus Aureus (MRSA) 3(13.04%) and single case of Enterobacter spp. In environmental samples, K. oxytoca and Enterobacter spp. were isolated. Amikacin, Imepeneum and Ciprofloxacin were sensitive whereas Ampicillin in combination with Cloxacillin, Ampicillin, Aztreonam were resistant for Klebsiella. oxytoca. Amikacin, Ceftazidime and Imipenuem are sensitive to Enterobacter spp. The single or combinations of resistant antibiotics were found to be prescribed. Conclusion The emerging antibiotic resistances among the culture isolates and coherence with environmental samples were observed. Hence, special measures are imperative for reducing environmental contamination and the rational usage of antibiotics for preventing the infection and emerging antibiotic resistance. The study recommends need of the antibiotic policy to curb the present scenario. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 27-32 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7339